Beyond Economic Growth: Does Natural Gas Consumption and Price Promote Trade in Top Gas Producing African Nations?- An Evidence from Time Series Analysis - (:unkn) unknown (My University, 2024)
The study examined the role of natural gas consumption and price in enhancing trade among top gas producing nations in Africa. To accomplish the study's objective, data on natural gas consumption, natural gas price, and gasoline motor fuel (used as a reference variable) was gathered from the World Bank and the International Energy Agency. These data were then analysed using the panel ARDL methodology to examine the relationship between trade openness and natural gas consumption and price in the six leading gas producing nations in Africa – Nigeria, Angola, Algeria, Egypt, Libya, and Gabon. The findings of our study indicates that a rise in the price of natural gas has a positive impact on the trade and growth levels in the economies of the leading gas-producing nations in Africa. As the price rises, there is a corresponding increase in commerce, particularly in exports. This leads to a growth in real GDP and a greater contribution of the energy sector to the overall economic development. The increase in trade and economic development leads to greater trade openness, with the price of natural gas playing a crucial role in this improvement. The trade facilitation in the chosen African nations that produce natural gas was greatly hindered by the high prices of natural gas (natural gas consumption) and the usage of petrol for vehicle fuel. Based on these findings, the study suggested that: liberalising the oil and gas sector in gas producing nations would be beneficial to their economy. This would encourage competition, stabilise prices, strengthen gas infrastructure, and boost trade and development in gas producing nations in the African sub region.
Keywords: African Research